Efforts To Improve The Reading Skills of 2nd Graders by Applying Demonstration Methods - Budiyaningsih, Elisabeth (Universitas Sebelas Maret, 2020)
Reading is a very important language skill in life. Cultured and educated people make reading a necessity in communicating. By reading learners will easily gain knowledge and insight from anywhere. Based on the above it can be concluded that without the ability to read well, then learners will not be able to understand the learning process and the material taught. The use of demonstration methods is expected to improve the reading skills of 2nd grade learners in SDN 3 Tirtomoyo District Tirtomoyo Wonogiri Regency.